Bromine Cation Initiated vic-Diphosphination of Styrenes with Diphosphines under Photoredox Catalysis - Otomura, Nobutaka; Okugawa, Yuto; Hirano, Koji; Miura, Masahiro (Synthesis, 2018)
An N-bromosuccinimide (NBS)-initiated vic-diphosphination of styrenes with diphosphines proceeds under visible-light-promoted Ir(ppy)3 photoredox catalysis to deliver the corresponding 1,2-diphosphinoethane derivatives in good yields. The NBS is a bromine cation source and generates a bromophosphine, which undergoes a single-electron reduction by the excited iridium species to form phosphinyl radicals of key species in the diphoshination reaction. The newly developed photoredox catalysis demonstrates better reaction efficiency, functional group compatibility, and scalability than the previous photocatalysis using N-fluorobenzenesulfonimide (NFSI) and silylphosphine.
Keywords: diphosphination; diphosphine; ligand; photocatalyst; styrene